2018
DOI: 10.1002/smll.201802081
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Determination of the pH inside the Confinement of a Virus‐Like Particle

Abstract: In biology, a variety of highly ordered nanometer-size protein cages is found. Such structures find increasing application in, for example, vaccination, drug delivery, and catalysis. Understanding the physiochemical properties, particularly inside the confinement of a protein cage, helps to predict the behavior and properties of new materials based on such particles. Here, the relation between the bulk solution pH and the local pH inside a model protein cage, based on virus-like particles (VLPs) built from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 58 publications
2
42
0
Order By: Relevance
“…Interestingly, a similar phenomenon was found for the nanosized viral protein cage in a certain pH range, which contains pores on the protein shell and allows ions to freely diffusing in and out. 47 By shiing the Pdot-HTPS pH response, it can be noted that it follows the same trend as free probes (see empty blue square in Fig. 2a).…”
Section: Physiochemical Environment Of Hollow Polymer Vesiclesmentioning
confidence: 69%
See 1 more Smart Citation
“…Interestingly, a similar phenomenon was found for the nanosized viral protein cage in a certain pH range, which contains pores on the protein shell and allows ions to freely diffusing in and out. 47 By shiing the Pdot-HTPS pH response, it can be noted that it follows the same trend as free probes (see empty blue square in Fig. 2a).…”
Section: Physiochemical Environment Of Hollow Polymer Vesiclesmentioning
confidence: 69%
“…45,46 HTPS has a highly sensitive pH-dependent absorption shi, allowing ratiometric measurements by taking a ratio of uorescence intensity at emission of l ¼ 515 nm with excitation at l ¼ 455 nm and l ¼ 402 nm. 47 Moreover, HTPS does not permeate through membranes, 43 which results in stable Pdots-HTPS hybrid nanoparticles (NPs) suitable for analysis. Encapsulation of HTPS inside the Pdots was performed by a method similar to the preparation of Pdots.…”
Section: Physiochemical Environment Of Hollow Polymer Vesiclesmentioning
confidence: 99%
“…The GALT confinement in the BMV capsid is higher that these obtained in P22 VLPs containing cytochrome P450 that was 3.14 mM [63] and higher than the 1 mM obtained in a lipase encapsulated in CCMV capsids [67] . In addition, it has been previously reported that local pH inside CCMV (which shares some sequence identity to BMV) is 0.5 unit more acidic compared to the bulk pH [68] . This acidic difference could reduce the GALT activity inside BMV [69]…”
Section: Discussionmentioning
confidence: 99%
“…[67] In addition, it has been previously reported that local pH inside CCMV (which shares some sequence identity to BMV) is 0.5 unit more acidic compared to the bulk pH. [68] This acidic difference could reduce the GALT activity inside BMV. [69]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, reducing the mobility of ionic species in the samples possibly also reduces the systems entropy. 46…”
Section: Pss-templated Assemblymentioning
confidence: 99%